Christology in Cultural Perspective : Marking out the Horizons - Greene, Colin J. D. (Grand Rapids, Mich. : William B. Eerdmans Pub., 2004)
"This volume by Colin Greene explores the interfaces between successive cultural contexts and the story of Jesus to which the Scriptures bear witness."--Jacket.
Christology-the nature of the task -- Three christological trajectories -- The engagement with modernity; the search for cultural paradigms. Christology and the enlightenment -- Christology and religious experience -- Christology and history -- Christiology and self-transcendence -- Christology and human liberation -- Christology and gender -- The engagement with postmodernity : deconstructing the cultural paradigms. Christology and the end of the enlightenment -- Jesus Christ the true paradigm -- The engagement with postmodernity-Christology on the way -- And where to now?
Originally published: Carlisle, Cumbria, UK : Paternoster Press, 2003.
Includes bibliographical references (pages 387-411) and indexes.
Keywords: Jesus Christ -- History of doctrines; Christianity and culture -- History